FESTIVAL BUDAYA ISEN MULANG SEBAGAI UPAYA PROMOSI PARIWISATA BUDAYA DI PROVINSI KALIMANTAN TENGAH - Saputra, Putu Wisnu; Suparta, Ida Kade (Paryaṭaka Jurnal Pariwisata Budaya dan Keagamaan, 2023)
This study uses a qualitative approach to obtain clear descriptions related to the implementation of the Isen Mulang cultural festival as an effort to promote cultural tourism. Isen Mulang is an annual agenda for the Palangkaraya tourism office as a series of activities to celebrate the anniversary of Central Kalimantan Province. As a result of the Covid-19 pandemic, the Isen Mulang cultural festival has not been held for two years considering that all Indonesian people, especially Central Kalimantan, have restricted their activities. With several considerations, finally in 2022 this activity will be held again in the City of Palangka Raya with the theme "Harmony in Cultural Diversity in Bumi Isen Mulang". The Isen Mulang cultural festival features a variety of cultural arts including regional dances, traditional clothing, and various ornaments typical of cities and regencies in Central Kalimantan. Various types of competitions were also held to enliven the event. The Isen Mulang cultural festival is used as a promotional momentum in the rise of the world of tourism in Central Kalimantan. This festival aims to popularize the diversity of Central Kalimantan's cultural arts at the national and international levels in carnival packaging, as well as one of the activities to bridge the preservation of Central Kalimantan culture.